ASUHAN KEPERAWATAN PADA KLIEN NY. D (G2P1A0) DENGAN HIPEREMESIS GRAVIDARUM - Chandra Kirana Asokawati, (2022)
Mrs. D, 28 years old with 21 weeks of gestation, entered the second trimester with complaints of nausea, vomiting and heartburn, Mrs. D looks limp, and the mucosa is dry. Excessive nausea and vomiting/hyperemesis gravidarum during pregnancy requires attention because of its negative effects on pregnancy, childbirth. The study was conducted to determine the causative factors and how to treat Hyperemesis Gravidarum with nursing care in order to reduce the incidence and risk due to Hyperemesis Gravidarum. This research method uses a case study method in nursing care for Ny. D (G2PIA0) with hyperemesis gravidarum in regency 1 RT/RW 001/005 Cibitung, Bekasi Regency. West Java on the stairs; June 16, 2021 to June 18, 2021. Data collection is done by interview, observation and physical examination, as well as documentation. Results: the main nursing diagnosis is nutritional imbalance: less than body requirements related to excessive output marked nausea and vomiting. Nursing interventions are carried out by nutritional management. Implementation of nursing actions according to priorities that have been made and equipped with interventions from the next diagnosis. Within 3 x 24 hours the problem of excessive nausea and vomiting can be resolved. Conclusion: the care given by Mrs. D based on nursing care can be resolved, Mrs. D is no longer nauseous and vomiting, and Mrs. D already understands what Hyperemesis Gravidarum is and how to treat it